1955
DOI: 10.1172/jci103181
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of Urinary Adrenocortical Steroids in Adrenal Hyperplasia 1

Abstract: Following the demonstration by Wilkins, Lewis, Klein, and Rosenberg (1) that cortisone controls the clinical manifestations and abnormal laboratory findings in virilizing adrenal hyperplasia, Bartter, Albright, Forbes, Leaf, Dempsey, and Carroll (2) postulated a deficient synthesis of "sugar hormone" (17-hydroxycorticosterone, Compound F) in this disease, reasoning from the unusual response of such patients to the administration of adrenocorticotropin (ACTH). This hypothesis has been supported by the demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1956
1956
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…In accordance with the scheme of adrenocorticosteroid biogenesis suggested by Hechter and his coworkers (25), Jailer has suggested that a block exists in the conversion of 17a hydroxyprogesterone into compound F (17). Substantiation of Jailer's hypothesis has been given by the demonstration by Bongiovanni and his'co-workers that 3a-17c-20a-pregnanetriol is the steroid found in greatest quantity in the urine of affected patients (6,7,26,27). In addition, administration of ACTH to patients with adrenal hyperplasia has caused a rise in urinary pregnanetriol, frequently of greater magnitude than the increase of 17-ketosteroids (7,26).…”
Section: Expression In Possible Heterozygotesmentioning
confidence: 78%
“…In accordance with the scheme of adrenocorticosteroid biogenesis suggested by Hechter and his coworkers (25), Jailer has suggested that a block exists in the conversion of 17a hydroxyprogesterone into compound F (17). Substantiation of Jailer's hypothesis has been given by the demonstration by Bongiovanni and his'co-workers that 3a-17c-20a-pregnanetriol is the steroid found in greatest quantity in the urine of affected patients (6,7,26,27). In addition, administration of ACTH to patients with adrenal hyperplasia has caused a rise in urinary pregnanetriol, frequently of greater magnitude than the increase of 17-ketosteroids (7,26).…”
Section: Expression In Possible Heterozygotesmentioning
confidence: 78%
“…A deficiency of 21-hydroxylation has been reported in both the nonsalt-losing and the salt-losing forms of congenital adrenal hyperplasia (1)(2)(3)(4). Cortisol and aldosterone, the two biologically significant steroids secreted by the human adrenal cortex, require 21-hydroxylation for their biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…CAH due to 21-hydroxylase deficiency was first accepted in 1955 5 and now constitutes a spectrum of disease with varying severity and biochemical features consistent with expression of mutations in the CYP21A2 gene. The laboratory often gets requests for 17-OHP during investigations of patients with androgen excess.…”
Section: Introductionmentioning
confidence: 99%